Study on Transduodenal Migration of Pancreatic Duct Stent into Liver - D. Samprathi (Issues and Developments in Medicine and Medical Research Vol. 9, 2022)
Endoscopic Retrograde Cholangio-pancreatography(ERCP) is the one of the modality for treating symptomatic pancreatic duct obstruction with dilation and stent placement. A duodenal perforation caused by pancreatic plastic stent migration into the liver has not been reported. When the contents of the intestine leak into the peritoneal cavity, it causes perforative peritonitis. However, stent migration leading to duodenal perforation is a slow process in which inflammation causes adherence of surrounding organs, preventing leakage of intestinal contents into the free peritoneal cavity. We present a case of contained duodenal perforation caused by pancreatic stent migration into the liver.